Audiovizualinės istoriografijos atvejis Lietuvoje: televizijos laida „Būtovės slėpiniai" - Šermukšnytė, Rūta (Lietuvos istorijos studijos, 2007)
This article defends the thesis that cooperation between science and audio-visual methods can become close enough to occasion the appearance of an audio-visual historiography, analogous to visual anthropology (in other words, ethnographic film), which is considered an independent form of presenting the process of inquiry under the governance of scientific methodologies.The article discusses currently existing concepts of audio-visual historiography, defines the criteria for the identification of audio-visual historiography and presents the example of the Lithuanian television show "Būtovės slėpiniai" shown from 1993 to 2004. This television show is an example of the phenomenon of "Lithuanian" audio-visual historiography. It is said that the theoretical discourse in other countries includes two concepts of audio-visual historiography, one of which defines audio-visual historiography mainly through aesthetic criteria, whereas the other, while not denying the importance of aesthetic criteria, places requirements for the traditionally understood scientific recognition of the past first. Combining these concepts into one, a collection of audio-visual criteria emerges, upon which analysis of the show "Būtovės slėpiniai" is based. The analysis shows that "Būtovės slėpiniai" can be considered a representative of visual historiography.